The future of the past in South African schools : curriculum development, school leaving examinations and syllabus design and assessment in history : a comparative study - Gunn, Alan Howard (Rhodes University, Faculty of Education, Department of Education, 1990)
This is a two-part study dealing with the curriculum, school leaving examinations and History as a school subject in England and South Africa. Part One is a developmental study. Developments in the curriculum of both countries since the Second World War are traced. In England this period is characterised by a shift from a somewhat laissez faire approach of the authorities at Whitehall to the curriculum of individual schools to the prescription that seems inherent in the National Curriculum. The outstanding development in South Africa during this period has been the introduction of a system of differentiated education. In contrast to minor developments in the South African school leaving examination system, England has witnessed the consolidation of the two-tier GCE and CSE system into a single examination at 16+, the GCSE. In discussing developments in History as a school subject, one is struck by the growth of the "new history" in England (this is described in some detail) against the relative lack of development (at "official" syllabus level) in South Africa where the subject remains rooted in the "traditional", chronological, content-based approach. Part Two of this study compares the current situation in England and South Africa at both the macro (ie. curriculum and school leaving examination systems) and micro (ie. History as a subject in the curriculum) levels. At the macro level the curriculum and school leaving examination systems in both England and South Africa are contrasted and one notes an increasing trend towards centralization in both countries. At the micro level use is made of "official" syllabuses and examination papers to contrast the "new history" approach in England with the "traditional" approach in South Africa. In the conclusion two broad possibilities for curriculum reform in South Africa are considered: Broad reform across the curriculum on the one hand and reforms in History on the other
Keywords: Education -- South Africa; Education -- South Africa -- History; Education -- South Africa -- Forecasting